A Small GTPase, RhoA, Inhibits Bacterial Infection Through Integrin Mediated Phagocytosis in Invertebrates - Xu, Ji-Dong; Diao, Meng-Qi; Niu, Guo-Juan; Wang, Xian-Wei; Zhao, Xiao-Fan; Wang, Jin-Xing (Frontiers in Immunology, 2018)
The Ras GTPase superfamily, including more than 100 members, plays a vital role in a number of cellular processes, such as cytoskeleton recombination, gene expression, and signaling pathway regulation. Some members of the superfamily participate in innate immunity in animals. However, there have been few studies of RhoA on this aspect. In the present study, we identified a RhoA GTPase in the shrimp Marsupenaeus japonicus and named it MjRhoA. Expression of MjRhoA was significantly upregulated in hemocytes and heart of shrimp challenged with Vibrio anguillarum. Overexpression of MjRhoA in shrimp caused the total bacterial number to decrease significantly and knockdown of MjRhoA increased the bacterial number obviously, with a consequent decline in shrimp survival. These results confirmed the antibacterial function of MjRhoA in shrimp. Further study showed that rate of phagocytosis of hemocytes was decreased in MjRhoA-knockdown shrimp. Interestingly, we observed that MjRhoA moved to the hemocyte membrane at 1 h post V. anguillarum challenge. The expression levels of the -integrin-mediated phagocytosis markers ROCK2 and Arp2/3 declined significantly after knockdown of MjRhoA. These results suggested that the antibacterial function of MjRhoA was related to -integrin-mediated phagocytosis in shrimp. Our previous study identified that a C-type lectin, FcLec4h, initiated -integrin mediated phagocytosis after bacterial infection. Thus, knockdown of FcLec4h and -integrin was performed. The results showed that the translocation of MjRhoA from the cytoplasm to membrane was inhibited and the expression level of MjRhoA was decreased, suggesting that MjRhoA participated in FcLec4h-integrin mediated phagocytosis. Therefore, our study identified a new FcLec4h-integrin-RhoA dependent phagocytosis against bacterial infection in shrimp.